2018
DOI: 10.1007/s10461-018-2049-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Providers’ Self-Efficacy and Intentions to Provide Safer Conception Counseling Over 24 Months

Abstract: High rates of fertility desires, childbearing and serodiscordant partnerships among people living with HIV (PLHIV) in Uganda underscore the need to promote use of safer conception methods (SCM). Effective SCM exist but few PLHIV benefit from provider-led safer conception counseling (SCC) and comprehensive national SCC guidelines are still lacking. Providers' self-efficacy, intentions and attitudes for SCC impact provision and should inform development of services, but there are no longitudinal studies that ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Clinicbased tablet applications may be especially important for fertility tracking among HIV serodiscordant couples who desire provider reassurance and counseling about their peak fertility timing for condomless sex (14). In addition, HIV providers frequently report desires for increased training on safer conception counseling and have described difficulties integrating HIV prevention messages into family planning and reproductive health service delivery (48)(49)(50). SCIP study clinicians and counselors regularly used the clinic-based tablet application during counseling sessions and found that it enhanced patient-provider communication.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicbased tablet applications may be especially important for fertility tracking among HIV serodiscordant couples who desire provider reassurance and counseling about their peak fertility timing for condomless sex (14). In addition, HIV providers frequently report desires for increased training on safer conception counseling and have described difficulties integrating HIV prevention messages into family planning and reproductive health service delivery (48)(49)(50). SCIP study clinicians and counselors regularly used the clinic-based tablet application during counseling sessions and found that it enhanced patient-provider communication.…”
Section: Discussionmentioning
confidence: 99%
“…Nine articles referenced reproductive rights for serodiscordant couples or women living with HIV and family planning 12–20. This was also referred to by some authors as the ‘right to bear children’.…”
Section: Resultsmentioning
confidence: 99%
“…39 This is supported by research showing that the degree to which an HCW considers themselves to be confident and competent performing a skill is associated with externally rated application of that skill in practice. 20,21 However, in the subset analysis of training interactions, external ratings were lower than HCW’s self-assessments, suggesting that confidence may not translate to objective competence. The patient actors rated providers especially low in communication skills, while technical reviewers noted deficiencies in clinical assessments and history-taking.…”
Section: Discussionmentioning
confidence: 98%
“…[18][19][20] Conversely, in a variety of global settings and across HCW cadres, high self-rated competence related to specific skills and content areas has been shown to be associated with accurate understanding of and willingness to discuss sensitive topics. [20][21][22][23] To inform optimal rollout of YFHS, this study examines training coverage, as well as the characteristics, facility context, and self-reported competence of HCWs working with ALWH in Kenya. An improved understanding of HCW training needs, as well as correlates of health worker competence related to adolescents, will inform training planning, with a vision toward higher quality YFHS services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation